2014
DOI: 10.1084/jem.20131738
|View full text |Cite
|
Sign up to set email alerts
|

Co-targeting of convergent nucleotide biosynthetic pathways for leukemia eradication

Abstract: Co-targeting of both de novo and salvage pathways for dCTP biosynthesis shows efficacy in T-ALL and B-ALL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 36 publications
2
53
0
Order By: Relevance
“…However, dCK is required for normal hematopoiesis (4) and DNA damage response (5). Moreover, dCK provides an escape mechanism when DNA de novo synthesis is inhibited by ribonucleotide reductase inhibitors (6). This resistance can be overcome using small-molecule inhibitors of dCK (6)(7)(8)(9).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, dCK is required for normal hematopoiesis (4) and DNA damage response (5). Moreover, dCK provides an escape mechanism when DNA de novo synthesis is inhibited by ribonucleotide reductase inhibitors (6). This resistance can be overcome using small-molecule inhibitors of dCK (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Moreover, dCK provides an escape mechanism when DNA de novo synthesis is inhibited by ribonucleotide reductase inhibitors (6). This resistance can be overcome using small-molecule inhibitors of dCK (6)(7)(8)(9). dCK is also required to phosphorylate and activate inactive prodrugs such as cytarabine, gemcitabine, decitabine, and cladribine (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To accommodate this demand, cells can produce dNTPs either de novo from metabolic precursors, including glucose and glutamine, or by salvaging deoxynucleosides from the extracellular milieu (47). Although still incompletely understood, it is likely that malignant cells favor de novo dNTP synthesis over salvage but can switch between the two for DNA replication, depending on environmental factors (48).…”
Section: Nucleotide Metabolismmentioning
confidence: 99%
“…However, it is important to note that cells not only synthesize nucleotides but can also scavenge them from the environment. In fact, a recent study revealed that the efficiency of chemotherapeutic strategies targeting nucleotide biosynthesis is greatly enhanced by simultaneously targeting the nucleotide savage pathway [102]. The need of cancer cells to maintain a healthy pool of dNTPs is highlighted by the recent discovery of inhibitors of the MTH1 enzyme, responsible for sanitizing oxidized nucleotides in the cells.…”
Section: Targeting Rs In Cancer Treatmentmentioning
confidence: 99%